The Misyar Marriage and Family Law Reform in Indonesia - Pelangi, Intan; Angkasa, Nitaria; Arifin, Syamsul (SMART: Journal of Sharia, Traditon, and Modernity, 2023)
This article aims to examine the thought of misyar marriage according to Yusuf Al-Qardhawi, and aims to prohibit the practice of misyar marriage in Indonesia. So this research examines the law of misyar marriage from Al-Qardawi's perspective and its contribution to the reform of family law in Indonesia.  This article includes library research. This research is descriptive analytical. The primary data in the research are the Qur'an, Hadith, Yusuf Al-Qardhawi's works, Law Number 1 of 1974 concerning National Marriage Law, and the Compilation of Islamic Law. The secondary data are scientific works, research, journals that are relevant to the research topic. Using Gustav Redbruch's theory of legal objectives and maslahah mursalah, the data analysis in this study uses inductive thinking techniques then the author makes data analysis with qualitative analysis. The result of this article is that misyar marriage according to Al-Qardhawi is a marriage that is not in accordance with the purpose of the ordinance of marriage, namely to form a family that is sakinah mawaddah and rahmah, but there is a gap in Law Number 1 of 1974, concerning Marriage in Article 2 Paragraph (1) "Marriage is valid, if it is carried out according to the laws of each religion and belief". When referring to this article, it can be said that it is valid, so that in order to provide assertiveness to prohibit the practice of misyar marriage and marriage practices that are not in line with the principles of marriage, it is necessary to provide a clear definition of marriage. Keyword: Misyar; Yusuf Al-Qardhawi; Family Law in Indonesia